Consumer Commitment: Theoretical Review of the Concept and its Background (REGE Revista de Gestão, 2013)
Consumer behavior is changing in recent decades, especially concerning its influence on organizations. Managers and researchers recognize the changes in the relationship between business and consumers, and one of the factors that contribute to this process is the commitment. In the last decade, this issue has been inserted in some disciplines, including in the field of marketing studies, focused on committed relationship between the company and the customer/consumer. In this study, it was possible to see the evolution of this concept, despite some uncertainties in relation to the mental construction. The aim of the study was to develop a theoretical review of the subject, so that an integrative concept and the determining factors for the development of the customer/consumer’s commitment were clearly identified. The definitions and conceptual models developed by Vivek (2009), van Doorn et al. (2010), Brodie et al. (2011) and Hollebeek (2011a) were the main contributions concerning commitment. From these studies, it was possible to have a critical and integrator view of the key concepts related to the subject and its background.